Evaluation of modern large-vocabulary speech recognition techniques and their implementation - Swart, Ranier Adriaan (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.